2007
DOI: 10.1099/ijs.0.65240-0
|View full text |Cite
|
Sign up to set email alerts
|

Desulfatiferula olefinivorans gen. nov., sp. nov., a long-chain n-alkene-degrading, sulfate-reducing bacterium

Abstract: A novel anaerobic, long-chain alkene-degrading, sulfate-reducing bacterium, strain LM2801T, was isolated from brackish sediment of a wastewater decantation facility of an oil refinery (Berre lagoon, France). Cells of strain LM2801T were Gram-negative, motile, slightly curved or vibrioid rods. Its optimum growth conditions were 30–36 °C, 6–10 g NaCl l−1 and pH 7.5. Strain LM2801T incompletely oxidized long-chain alkenes (from C14 to C23) and fatty acids (C14 to C24). The DNA G+C content was 45.5 mol%. Sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 13 publications
2
18
0
1
Order By: Relevance
“…Desulfobulbus species can ferment lactate and ethanol (plus carbon dioxide) to acetate and propionate in the absence of sulfate, and many Desulfovibrio and Desulfomicrobium species grow by fermenting pyruvate to form acetate, carbon dioxide, and hydrogen as products (51,54,55). In comparison, Desulforegula and Desulfatiferula were not detected in the inner layers, as the ability of these SRB to ferment organic matter is limited (49,57).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Desulfobulbus species can ferment lactate and ethanol (plus carbon dioxide) to acetate and propionate in the absence of sulfate, and many Desulfovibrio and Desulfomicrobium species grow by fermenting pyruvate to form acetate, carbon dioxide, and hydrogen as products (51,54,55). In comparison, Desulforegula and Desulfatiferula were not detected in the inner layers, as the ability of these SRB to ferment organic matter is limited (49,57).…”
Section: Discussionmentioning
confidence: 98%
“…However, in this study, we also observed the proliferation of SRB, which normally use on large-molecule organic substrates rather than on hydrogen, acetate, and propionate for growth. Desulforegula and Desulfatiferula are known to use long-chain fatty acids and long-chain alkenes to reduce sulfate (49,57). Also, some Desulfovibrio spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desulfatibacillum spp. [Callaghan et al, 2012;Cravo-Laureau et al, 2005], Desulfobacula toluolica [Wöhlbrand et al, 2013], Desulfotignum toluenicum [Ommedal and Torsvik, 2007] or Desulfatiferula olefinivorans [Cravo-Laureau et al, 2007], have been isolated and described. Some studies have shown the ability of sulfate reducers to grow syntrophically by fermentation when sulfate concentrations are too low.…”
Section: Microbial Ecology and Molecular Biology Of Methanogenic Hydrmentioning
confidence: 99%
“…Previous studies have reported the biodegradation of n-alkenes by mesophilic sulfate-reducing bacteria (namely, strains Hxd3 [1], Pnd3 [2], AK-01 [25], Desulfatibacillum aliphaticivorans strain CV2803 [11], Desulfatibacillum alkenivorans strain PF2803 [12], and Desulfatiferula olefinivorans strain LM2801 [10]). To our knowledge, this is the first report of the anaerobic oxidation of hydrocarbons, specifically n-alkenes, by a member of the domain Archaea and at a temperature as high as 70°C.…”
Section: Identification Of Perdeuterated Hexadecene-derived Fatty Acidsmentioning
confidence: 99%